2022
DOI: 10.3390/cancers14030713
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Features of the Spleen as Surrogates for CT-Based Lymphoma Diagnosis and Subtype Differentiation

Abstract: The spleen is often involved in malignant lymphoma, which manifests on CT as either splenomegaly or focal, hypodense lymphoma lesions. This study aimed to investigate the diagnostic value of radiomics features of the spleen in classifying malignant lymphoma against non-lymphoma as well as the determination of malignant lymphoma subtypes in the case of disease presence—in particular Hodgkin lymphoma (HL), diffuse large B-cell lymphoma (DLBCL), mantle-cell lymphoma (MCL), and follicular lymphoma (FL). Spleen seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Conversely, the degree of splenomegaly was reported as an inappropriate index in previous studies. [1,27] The splenomegaly had been defined as >13 cm in length in the long axis. [1,4] The feasibility of 13 cm in length for criteria of splenic involvement was investigated by Berzaczy et al, showing an accuracy of 74.1% and a specificity of 47%.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the degree of splenomegaly was reported as an inappropriate index in previous studies. [1,27] The splenomegaly had been defined as >13 cm in length in the long axis. [1,4] The feasibility of 13 cm in length for criteria of splenic involvement was investigated by Berzaczy et al, showing an accuracy of 74.1% and a specificity of 47%.…”
Section: Discussionmentioning
confidence: 99%
“…Another study used the spleen’s radiomics signature on CT to predict the recurrence of HCC [ 34 ]. Additionally, considering lymphoma, Enke et al developed a radiomics model on CT to differentiate between spleen involvement versus controls, as well as to discriminate different subtypes of malignant lymphoma [ 35 ]. Their results showed that the radiomics signature could predict the presence of malignant lymphoma with an AUC of 0.86, and even differentiate between subtypes with a satisfying AUC.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 1316 features were extracted per lesion. The features were not harmonized to account for different scanner types, as this has been shown to not improve model performance in previous work on CT-based features [ 20 ].…”
Section: Methodsmentioning
confidence: 99%